CRISPR knockout screening outperforms shRNA and CRISPRi in identifying essential genes - Evers, Bastiaan; Jastrzebski, Katarzyna; Heijmans, Jeroen P M; Grernrum, Wipawadee; Beijersbergen, Roderick L; Bernards, Rene (Nature biotechnology, 2016)
CRISPR knockout screens outperform shRNA and CRISPR-interference screens in a side-by-side comparison. High-throughput genetic screens have become essential tools for studying a wide variety of biological processes. Here we experimentally compare systems based on clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) or its transcriptionally repressive variant, CRISPR-interference (CRISPRi), with a traditional short hairpin RNA (shRNA)-based system for performing lethality screens. We find that the CRISPR technology performed best, with low noise, minimal off-target effects and consistent activity across reagents.